O gênero Butia (Becc.) Becc. (Arecaceae) no Rio Grande do Sul com ênfase nos aspectos ecológicos e silviculturais de Butia yatay (Mart.) Becc. e Butia witeckii K. Soares & S. Longhi - Soares, Kelen Pureza (2013)
The aim of this work was show two studies. The first one consisted of a survey on indigenous Butia from Rio Grande do Sul. Through observations of morphological characteristics, eight species were recognized (B. catarinensis Noblick & Lorenzi, B. eriospatha (Mart. ex Drude) Becc., B. exilata Deble & Marchiori, B. lallemantii Deble & Marchiori, B. odorata (Barb. Rodr.) Noblick, B. paraguayensis (Barb. Rodr.) L. H. Bailey, B. witeckii K. Soares & S. Longhi and B. yatay (Mart.) Becc.). Three were considered synonyms (B. missionera Deble & Marchiori, B. pulposa (Barb. Rodr.) Nehrl. and B. quaraimana Deble & Marchiori). B. microspadix Burret and B. stolonifera (Barb. Rodr.) Becc. was not confirmed from Rio Grande do Sul. Figures with geographical distribution, key of identification, illustrations, and comments about the biology and taxonomy of each species were provided. The second study evaluated the ecological characteristics and productive and reproductive potential of two jelly palm populations from Rio Grande do Sul, with a population of B. yatay species (from Coatepe Quaraí) and another of B. witeckii species (from Quebra-dentes Quevedos/Júlio de Castilhos). In an area of 1 ha of the first species and 2 ha of the second species, respectively 79 and 34 mature palms were found. The characterization of the number of fruits per inflorescence was based on a sample of 80 and 84 infructescenses, respectively of the B. yatay and B. witeckii species. The biometric characterization of the fruits was based on a sample of 240 and 360 fruits, respectively for the B. yatay and B. witeckii species, separated by crop and plot. The hypsometric distribution shows that two populations are seriously threatened due to lack of natural regeneration, predated by cattle. Both species showed some significant differences between biometric parameters in adult trees (except the stem circumference and number of inflorescences in B. witeckii) and their fruit, when comparing the different plots. Positive correlations were found between biometric parameters of plants and of the fruits. Biometric parameters of the palmtrees are correlate with ecological parameters observed. There was an increase in the production of fruit pulp in the year 2012 when compared with 2011 on two species.Several factors seem to influence productivity, such as weather conditions, performance of pollinators, age/size of palm, physical and chemical characteristics of the soil and density of reproductive plants. The productivity of pulp and viable seeds per adult palm shows significant difference between two species, 10.31 kg and 12.96 kg of pulp and 1388 and 1075 viable seeds per palm, respectively, for B. yatay and B. witeckii. The two species have great productive potential.